2019
DOI: 10.1186/s40425-019-0747-1
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral immunoglobulin isotypes predict survival in lung adenocarcinoma subtypes

Abstract: BackgroundThe role of tumor-infiltrating B-cells (TIBs) and intratumorally-produced antibodies in cancer-immunity interactions essentially remains terra incognita. In particular, it remains unexplored how driver mutations could be associated with distinct TIBs signatures and their role in tumor microenvironment.MethodsHere we analyzed associations of immunoglobulin isotypes and clonality with survival in TCGA RNA-Seq data for lung adenocarcinoma (LUAD), stratifying patients into 12 driver mutation and phenotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 66 publications
(93 reference statements)
1
58
0
Order By: Relevance
“…However, the other study showed that CD40-activated B cell was a vigorous antigen-presenting cell and was able to induce the effect of antitumor immunity (31). A recent study revealed a correlation between the amounts of tumor-infiltrating B cells and the survival of LUAD patients with specific mutation driver, which suggested that tumor-infiltrating B cells might be a symbol for the specific mutation in lung cancer cells (32). Therefore, the positive correlation between the amounts of B-cell memory and BTK expression in LUAD patients suggested that BTK might be responsible for the preservation of immune-active status in TME.…”
Section: Discussionmentioning
confidence: 99%
“…However, the other study showed that CD40-activated B cell was a vigorous antigen-presenting cell and was able to induce the effect of antitumor immunity (31). A recent study revealed a correlation between the amounts of tumor-infiltrating B cells and the survival of LUAD patients with specific mutation driver, which suggested that tumor-infiltrating B cells might be a symbol for the specific mutation in lung cancer cells (32). Therefore, the positive correlation between the amounts of B-cell memory and BTK expression in LUAD patients suggested that BTK might be responsible for the preservation of immune-active status in TME.…”
Section: Discussionmentioning
confidence: 99%
“…used genome-wide mRNA expression profile to establish the robust molecular subtypes of LUAD by using a combination method [ 32 ]. Many studies have also found different LUAD subtypes, which have different immune infiltration characteristics and molecular mechanisms [ 33 , 34 ]. More detailed genetic classification of tumors may be more effective for clinical precision therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Clonal expansions were identified only when comparing the samples obtained from X and Y fragments ( Figure 5C), and lower correlation of clonal frequencies between X and Y fragments compared to replicate samples allowed to estimate the level of immunoglobulin heterogeneity ( Figure 5D). Along with the composition, clonality, and hypermutation of intratumorally-produced antibodies, the proportion of distinct antibody isotypes may also be a crucial parameter with prominent prognostic value, as has been shown for human melanoma and subtypes of lung adenocarcinoma and bladder cancer (5,8). Like clonal frequencies, isotype proportions are heterogeneous across tumor tissue and subject to sampling noise, but also generally correlate well between replicates produced at the level of single-cell suspensions (Figure 5E).…”
Section: Measuring Intratumoral Clonal Heterogeneity Of B Cellsmentioning
confidence: 62%
“…Analysis of T and B cell repertoires has become a valuable and powerful tool for characterizing the immune response, complementing other high-content approaches such as transcriptome analysis and mass cytometry (1)(2)(3). Both T and B cell repertoires have been shown to be predictive of survival for cancer patients (4)(5)(6)(7)(8) and for assessing response to checkpoint immunotherapy (9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%